Comparison of distance covered, physiological cost, and perceived exertion in four six-minute walk test protocols - Muñoz-Cofré, Rodrigo; Sol, Mariano del; Lizana, Pablo A.; Gómez-Bruton, Alejandro; Fuentes Andaur, María José; Fierro, Erika Soto; Gonzalez, Gabriela Osorio; Medina-González, Paul; Valenzuela-Aedo, Fernando; Escobar-Cabello, Máximo (Frontiers in Physiology, 2024)
Objective: There is evidence that indicates that the Walked Distance (WD) in the 6-Minute Walk Test (6MWT) would be sensitive to the type of track and encouragement. The aim of study was compared the impact of track type and verbal encouragement provided in the 6MWT on WD, physiological cost, perceived exertion, and gait efficiency in healthy young adults unfamiliar with the test.Method: WD, heart rate, subjective sensation of dyspnea (SSD), and fatigue (SSF) were measured in four 6MWT protocols: i) 30 m linear track and protocolized encouragement (LT+PE), ii) 30 m linear track and constant encouragement (LT+CE), iii) 81 m elliptical track and protocolized encouragement (ET+PE), and iv) 81 m elliptical track and constant encouragement (ET+CE). In addition, the Gait Efficiency Index (GIE) associated with physiological cost, dyspnea and fatigue was calculated and compared between the different protocols.Results: The WD was significantly higher in the ET+CE protocol. The percentage of the heart rate reserve used (%HRRu) at minute 6 was higher in the ET+CE protocol. The SSD and SSD had difference in startup time between the protocols. The GEI was higher in %HRRu, SSD, and SSF for the ET+CE protocol. Conclusion: The ET+CE protocol showed a significant increase in WD during the 6MWT in healthy young adults. Although it obtained the highest physiological cost, it did not present perceptual differences when entering cardiopulmonary assessment windows relevant to a more efficient test for the participant. It is advisable to discuss, based on the findings, the fundamental objective of the 6MWT and national and international recommendations to achieve a result as close as possible to the real maximal effort.